O aspecto funcional dos gêneros textuais em livros didáticos para ensino de português como segunda língua - Natalia Moreira Tosatti (2009)
The aim of this research was to investigate the functionality of text genres present in five didactic books of Portuguese for Foreigners (PFL) published in the last decade. We analysed the didactic material based on the theory that distinguishes the genres as forms of action, such as ways to act in the world in relation to others in a culture and society. In our research, we investigated whether the present genre in the didactic books of Portuguese for Foreigners (PFL) being analyzed were explored in a functional way. That is, if they created situations of language practice that enabled the development of the communicative competence seen as a set of linguistic and pragmatic components related not only to the knowledge and skills necessary to the process of communication, but also related to the use and organization of the language in socio-cultural situations closer to reality, making the interaction with others easier. The results were obtained by means of an occurrence survey of genres in each one of the books. We concluded that the current didactic books of Portuguese for Foreigners, comprised in our corpus, presented a diversity of text genres in their units (lessons), although not always did the emphasis on the genre exploration lead to the communication process.This paper, using the exposition of data analysis and activities present, shows the way the genres have been explored in didactic books of Portuguese for Foreigners (PFL) published in the last ten years.